Facial Expression in Response to Smell and Taste Stimuli in Small and Appropriate for Gestational Age Newborns. (October 2015) - Rotstein, Michael; Stolar, Orit; Uliel, Shimrit; Mandel, Dror; Mani, Ariel; Dollberg, Shaul; Reifen, Ram; Steiner, Jacob E.; Harel, Shaul; Leitner, Yael
Small for gestational age newborns can later suffer from eating difficulties and slow growth. Nutritional preferences can be influenced by changes in sensory perception of smell and taste. To determine whether these could be detected at birth, the authors examined the different recognition pattern of smell and taste in small for gestational age newborns compared to appropriate for gestational age controls, as expressed by gusto-facial and naso-facial reflexes. The authors performed video analysis of facial expressions of 10 small for gestational age and 12 control newborns exposed to various tastes and smells. No difference in the facial recognition patterns for taste or smell was demonstrated between small for gestational age and controls, except for perception of distilled water. Newborns show recognizable patterns of facial expression in response to taste and smell stimuli. Perception of taste and smell in small for gestational age newborns is not different from controls, as measured by the method of facial recognition.